The Impact Of Competency Skills On Employees’ Performance In Construction Companies - Tay, Ee Lim (2022)
Employees is an important factor to a company. Without group of performance employees, a company unable to growth further. Training program to increase employee’s performance is relative important work to human resource management. Hard skill acting door key to enter certain industry, but soft skill enables them growth further. This study was studying how the competency skill impact to employee’s performance in a construction company. There are many skills that useful and promoting, this study is going to find out skills that more important and useful in construction company. This study was carried out in Klang Valley, which are having highest construction company quantity and highest project value among Malaysia. The five selected competency skill which are problem solving, communication, teamwork, negotiation, and leadership was tested positive relation to employee’s performance in construction company. This study also allowing us to identify which skill that most important for a team to enable the team’s heading success. This study may give a guideline to human resource management to plan for their employee’s skill development. The rank of important skill also may allow human resource management to have sequence of program planning.